Identification of progression related LncRNAs in colorectal cancer aggressiveness - Wei Xi; Xinxin Sun; Mingwei Wang; Xizi Wang; Kun Li; Runze Jiang; Xiaodong Jia; Wenxiao Wang (Scientific Reports)
Abstract Colorectal cancer (CRC) progression involves complex molecular alterations, including the dysregulation of long non-coding RNAs (lncRNAs). In this study, we identified key progression-related lncRNAs in CRC by integrating transcriptomic data from TCGA and single-cell RNA sequencing (scRNA-seq). Differential expression analysis revealed numerous lncRNAs associated with CRC progression. To systematically prioritize these lncRNAs, we developed a scoring system incorporating multiple progression-related signatures, differential expression, and survival analysis. This approach identified 198 key lncRNAs, including both known (e.g., LINC01615) and novel candidates (e.g., AC007998.3). Experimental validation confirmed that LINC01615 was significantly upregulated in CRC tissues, whereas AC007998.3 was downregulated. Further analyses indicated that these lncRNAs influence CRC progression through cis-, trans-, and post-transcriptional regulation. Patients were classified into distinct molecular subgroups based on lncRNA expression, exhibiting significant differences in prognosis and immune microenvironment composition. The enrichment of progression-related lncRNAs among differentially expressed lncRNAs was statistically significant, reinforcing their functional relevance. Validation across independent datasets demonstrated the robustness of our findings. Our research provides novel insights into the molecular mechanisms underlying CRC progression and highlights the potential of progression-related lncRNAs as prognostic biomarkers and therapeutic targets.